NFLUENCE OF LIFE CONDITIONS AND FAMILY EDUCATION STYLE ON COMMUNICATION OF PRESCHOOL CHILDREN WITH PEERS - Bashkireva T. V., In'kova P. M. (Psychology of Personal Interaction in Modern Society, 2024)
The article examines the problem of the influence of living conditions and upbringing of preschool children on their communication with peers. The age-related features of communication between preschoolers and peers are named. The results of diagnostics of preschool children aged 5-6 years are presented using the methods of L. Karman “Family Drawing”, “Mittens”, developed by G.A. Uruntaeva together with Yu.A. Afonkin and surveys of parents.
Keywords: дошкольники; общение; сверстники; preschoolers; communication; стиль семейного воспитания; peers; conditions and style of family education; условия семейного воспитания